THE INTERNATIONAL ARMS TRADE - Japhet, M. (Scientia Militaria - South African Journal of Military Studies, 2012)
Everyone is aware of the existence of the arms trade but few have any idea of the nature of its workings or of its implications, both actual and potential. Some information as to the methods employed in the sale of arms was made available via the Lockheed and Northrop scandals, but by and large this was information that could not be evaluated in terms of all the elements of the system. It is the aim of this article to provide some insight into the various facets that go together to make up the arms trade, in this way by no means giving an all-embracing account but merely providing some interesting facts and figures.